TOP-DOWN APPROACH IN CAPACITY BUILDING FOR TOURIST DESTINATION MANAGERS IN BOALEMO REGENCY, INDONESIA - Ghoriqna Fibahril Wahdah; Samin Latief; Ikram Muhammad (LP2M Universitas Bina Mandiri Gorontalo, 2022)
Management capacity building requires an effective approach in improving Tourist management practices in the region. This research aims to explain the implementation of a top-down approach in the program for Tourist destination managers and the level of its effectiveness in Boalemo Regency. This research is conducted by using descriptive evaluative design trough qualitative and quantitative approaches. The results showed that the top-down approach provided a low level space of participation for participants because the program was designed, directed and controlled from top side. This approach has proven only effective in the process of program implementation, but less effective at the follow-up stage caused by relevance of material, participants, capacity and authority